BREAKING THE ICE IN THE CLASSROOM: USING ICE BREAKING IN THE TEACHING AND LEARNING PROCESS - Fitria, Tira Nur (Universitas Borneo Tarakan, 2023)
This research describes ice-breaking (ice breaker) and the importance of ice-breaking in the teaching and learning process. This research is library research. The analysis shows that using ice-breaking requires preparation and planning, including materials, methods, and media. Ice-breaking usually can be used as warm-up activity at the beginning of learning. Ice-breaking must generate favorable impressions of students. Besides, the teacher must have strong impulses when delivering ice-breaking, must be sensitive to the classroom environment, adaptable to the student’s condition, and facilitate the students' needs. The teacher has the authority to vary or modify the game varieties of ice breaking while ensuring the duration needed. The ice-breaking is not only creating a joyful environment but also providing meaning and relevance to the subject material being presented. Icebreaker activities can be an effective way to create a comfortable and interactive learning environment in the classroom. They break the ‘ice’ to create a relaxed and positive atmosphere, allow students to feel comfortable, interact with classmates, open their minds to a more effective learning process, and solve students' concentration, absorption, learning interests, attention, motivation even learning outcomes. Ice-breaking activities can be applied to all subjects and can be combined with learning methods or other game techniques. The teacher as a learning facilitator may not leave the learning principles including learning how to learn, how to think, how to do, and how to live together. For teachers, preparing ice breaking in learning is the same as upgrading teachers’ pedagogical, personal, social, and professional competencies.